Derivation and Application of a Generalized Correlation for Mass Transfer in Packed Beds. Issue 4 (1st February 2017) - Reichelt, Erik; Jahn, Matthias; Lange, Rüdiger
Abstract: A generalized correlation for mass transfer in packed beds is developed. It is derived from considerations on single sphere mass transfer. The correlation is validated over a wide range of Reynolds numbers, Schmidt numbers, and bed porosities with literature data. Particular attention is paid to gas‐solid mass transfer at low Reynolds numbers where own experimental results are presented. With the help of the developed correlation, the influence of different bed properties and axial dispersion on mass transfer is discussed. Abstract : Mass transfer plays an important role in several industrial processes. The existing models for its description are rarely applicable, especially for gas‐solid mass transfer at low Reynolds numbers (Re). A generalized correlation for packed beds is presented. The validity for a wide range of Re, Schmidt numbers, and bed porosities is proven by literature data and own experimental results.